(untitled) (Damascus University Journal for engineering sciences, 2023)
The computational gait analysis was expected to reveal differences in gait parameters between the two genders. The aim of this study was to investigate the existence of sex-related differences in gait patterns in healthy Syrian middle aged adults when they walked at their normal speed. Fourteen healthy middle aged adults (8 females, 6 males) aged 35 to 55 years volunteered to complete this study. Spatio-temporal parameters and sagittal kinematic and kinetic data were obtained and analyzed using six cameras Smart-D optoelectronic motion capture system (BTS, Milan, Italy), and two force plates (Kistler,Switzerland) in biomechanical laboratory in Bioengineering department, Faculty of mechanical and Electrical Engineering at Damascus university. The statistical study was conducted using the SPSS statistical program. The results showed that the females had significantly 23% slower gait speed, 21% shorter stride length, 21% narrower step width. They walked with significantly more anteriorly pelvic tilt throughout whole gait cycle, 26% greater hip joint flexion at opposite toe-off event, 11% less hip joint extension at heel rise event, 32% greater Mean hip flexion during the whole swing phase, 3% greater ankle plantarflexion pre swing, and 30% smaller ankle dorsiflexion moment. There were significant differences in hip and ankle range of motion (ROM) between the two sexes. These sex differences in gait patterns indicate the importance of taking sex into account when interpreting and treating pathological gait as well as when developing reference gait parameters databases.